Religious coping and young adult's mental well-being during Covid-19: Testing a double moderated mediation model. (November 2022) - Fatima, Shameem; Arshad, Mahnoor; Mushtaq, Mamoona
The literature describes religious coping as an important predictor of mental well-being. Present study is aimed at extending this knowledge by assessing whether specific religious coping regulates specific cognitive emotional responses to improve well-being during Covid pandemic, an extreme international event with significant impacts on individuals and communities. A sample of young adults responded to self-report measures of negative and positive religious coping, positive reappraisal, self-blaming, and mental well-being. Results revealed that positive religious coping was a positive predictor of mental well-being and positive reappraisal mediated this positive link. Also, gender and physical health status significantly interacted with positive reappraisal to predict mental well-being in these mediational associations. More specifically, indirect effects of positive reappraisal were positive and significant for men and for participants with better physical health compared with women and those with poor physical health. However, negative religious coping was not a significant correlate of mental well-being but a positive correlate of self-blame. Results suggest that positive religious coping facilitates positive regulation of emotions for improved mental well-being in young adults and particularly young men.